2001
DOI: 10.1007/bf02345147
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the single equivalent point dipole model to represent a spatially distributed bio-electrical source

Abstract: Although the single equivalent point dipole model has been used to represent well-localised bio-electrical sources, in realistic situations the source is distributed. Consequently, position estimates of point dipoles determined by inverse algorithms suffer from systematic error due to the non-exact applicability of the inverse model. In realistic situations, this systematic error cannot be avoided, a limitation that is independent of the complexity of the torso model used. This study quantitatively investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 26 publications
0
38
0
2
Order By: Relevance
“…A spatial criterion was imposed to force solutions to land inside a predefined volume that includes the heart [1][2][3]8]. In prior studies [2,3] we have learned that the algorithm is convergent to a global minimum and hence is terminated, if two solutions that start from two different seeds are found to be closer than 0.5 cm.…”
Section: The Algorithm For the Inverse-problem Estimationmentioning
confidence: 99%
See 3 more Smart Citations
“…A spatial criterion was imposed to force solutions to land inside a predefined volume that includes the heart [1][2][3]8]. In prior studies [2,3] we have learned that the algorithm is convergent to a global minimum and hence is terminated, if two solutions that start from two different seeds are found to be closer than 0.5 cm.…”
Section: The Algorithm For the Inverse-problem Estimationmentioning
confidence: 99%
“…In the inverse algorithm, we used the SEMD model embedded in an infinite homogeneous volume conductor [1,2]. Then, the potential / i at location r i (x i , y i , z i ) on the body surface due to the dipole at r 0 (x 0 , y 0 , z 0 ) with moment p (p x , p y , p z ) in an infinite medium of conductivity g, was given by…”
Section: The Algorithm For the Inverse-problem Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In subsequent computational studies [12]- [14] in which we estimated the accuracy of the guiding process as the tip of the ablation catheter approaches the target site, we observed that despite differences in the systematic error across the left and the right ventricles, for a target site anywhere on the endocardial ventricular wall, our algorithm has been able to guide the catheter tip very close to the target site, the absolute error is ∼0.2 cm, which is appropriate for RCA procedures.…”
Section: Introductionmentioning
confidence: 99%